Algoritmo genético aplicado ao planejamento do uso do solo com vistas à qualidade ambiental e retorno econômico - Dambroz, Carlos Silva (2018)
Land use planning is a complex activity that considers both environmental and socioeconomic factors. In a degradation scenario, strategies should be developed that allow the best use of natural resources and avoid its overexploitation. This work aimed to develop a method to be applied in catchments land use planning at a pixel level. The environmental variables, soil loss and water surplus, and the economic variable, gross income, were considered in an optimization process. The optimization was implemented through Genetic Algorithm in association with the use of the Analytic Hierarchy Process method. The method was applied in four different regions using different scenarios for evaluation. The developed method is an efficient tool to support decision making in environmental planning. The technique presents flexibility to be adopted in regions with very distinct physical characteristics and to achieve the local decision makers demand.